Aspects of the Norm. The Holistic Model of the Legal Norm in the Context of Wittgenstein’s Remarks on Aspect Perception - Graboń, Wojciech (Hybris, 2019)
In Polish legal theory there is a generally accepted distinction between legal norms (normative standards) and legal provisions (independent editorial units of a legal text). One of the most developed theories of the interpretation of law, the derivative theory of M. Zieliński, however, also includes the postulate of the reconstruction of the entire legal system as one comprehensive norm (the so-called holistic approach) in the process of applying the law. This postulate stems mainly from assumptions regarding the adopted methods of interpretation. The holistic approach has often been criticized as inadequate in pragmatic terms, but the derivative theory has not yet been thoroughly modified in this respect. In this paper, I propose to apply Wittgenstein's concept of aspect perception as providing adequate conceptual framework to describe the mechanism of identifying relevant parts of the legal norm that deals with the pragmatic inadequacy of the holistic approach, but does not affect the core of the derivative theory of interpretation.